Consultorio Jurídico Gratuito de la Universidad de Otavalo - Maldonado, Ximena E. (2020)
The linkage project Free Legal Clinic of the University of Otavalo It started in the month of January of the year 2020 until November of the same year. It has as antecedent the integral evaluation carried out by the Public Defender's Office and as a result Satisfactory, the office is located in category "B" Accredited, in addition to the continuous improvement, an Improvement Plan was prepared for the operation of the Free Legal Office of the University of Otavalo that was developed in the year 2020, framed in the administrative management activities and the teaching process and learning for binding students and practitioners, whose activities consisted of: 1. Equitable distribution of binding students and interns by the coordinator of the Legal office and assignment of the tutor teacher, with its monitoring and follow-up respective. 2. According to the parameters established by the Public Defender's Office, the standards in their attention to priority attention groups. 3. The active and passive causes were archived in order to systematize the information of the causes, in order to obtain statistics both in sponsorship and advice in the matters accredited by the Public Defender's Office. 4. Several cases were reassigned to the student interns in order to follow up and quality service. 5. The regulations of the Legal Office were applied, complying with the powers of the staff. 6. Dissemination and training campaigns were carried out on the services provided by the Free Legal Office of the University of Otavalo. 7. Seminars, forums and virtual courses were developed jointly with the Ombudsman Public of Imbabura.